Worker Morale and Effort: Is the Relationship Causal? - Wolter Hassink; Roberto M. Fernandez (Institute for the Study of Labor (IZA), 2015)
We investigate a unique setting which enables us to distinguish between two theories of work performance. A standard labor supply framework implies a negative effect of the non-pecuniary cost of work on the employee's effort. In contrast, a model of worker morale that is consistent with a widely used theory of Akerlof and Yellen (QJE,1990) predicts this negative effect is stronger (weaker) for low-morale (high-morale) workers. We exploit a natural experiment design of a firm relocation from Milwaukee's Central Business District to the area's suburban ring in 1992. Since the employees did not choose the location of the new plant, there is an exogenous source of variation on the adjusted commuting distance among those who stay at the firm. Some of the workers received a windfall gain, whereas other workers experienced an unforeseen cost in longer commuting time. The estimates indicate that low-morale workers are responsive to the shock in commuting time. We conclude that the results favor the model of worker morale.
Keywords: J24; J31; M52; 330; natural experiment; absenteeism; worker morale